Symbolic Consumption of Crafts (Dimensión Empresarial, 2016)
This study approaches the factors associated with the symbolic consumption of crafts - ceramics and basket-making - of Ráquira and Guacamayas, objects that were exposed in Expoartesanías 2011, in the city of Bogota, and his relation with the construction of the national identity. The methodology of the investigation is quantitative with a descriptive multidimensional study, bearing the results of the survey in mind an analysis was realized lexicométrico - count of words - of conformities - importance - and his graphical representation in the plane factorial. The results allowed to identify the profile sociodemográfico, processes of consumption and the construction of identity related to the symbolic consumption of the above-mentioned crafts. In addition, and not less importantly it was the theoretical contribution to the concept of cultural consumption from his contradictions and possibilities.ResumenEste estudio aborda los factores asociados al consumo simbólico de artesanías –cerámica y cestería- de Ráquira y Guacamayas, objetos que fueron expuestos en Expoartesanías 2011, en la ciudad de Bogotá, y su relación con la construcción de la identidad nacional. La metodología empleada es cuantitativa bajo un estudio descriptivo multidimensional con base en los resultados de la encuesta, se realizó un análisis lexicométrico, de concordancias y representación gráfica. Los resultados permitieron identificar el perfil sociodemográfico, procesos de consumo y la construcción de identidad relacionada con el consumo simbólico de dichas artesanías. Además, y no menos importante fue el aporte teórico al concepto de consumo cultural desde sus contradicciones y posibilidades.ResumoEste estudo aborda os fatores associados ao consumo de -Ceramics artesanato simbólicos e cestería- Ráquira e araras, objetos que foram expostos em EXPOARTESANIAS 2011, na cidade de Bogotá, e sua relação com a construção da identidade nacional. A metodologia da pesquisa é estudo descritivo quantitativo, com um multidimensional, tendo em conta os resultados das lexicometrics análise de pesquisa -conteo de palavras de concordâncias -importancia- e sua representação gráfica no plano fatorial foi realizada. Os resultados permitiram identificar o perfil sócio-demográfico, os processos de consumo e a construção da identidade relacionada com o consumo simbólico destes ofícios. Além disso, e não menos a contribuição teórica foi o conceito de consumo cultural de suas contradições e possibilidades.
Keywords: symbolic consumption; crafts; identity; cultural consumption